Development of Artificial Live Rock in Supporting Ornamental Coral Cultivation Activities - Imam Safii; I Nyoman Dodik Prasetia; Gede Ari Yudasmara (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Artificial live rock is an artificial live rock that is shaped like living rock in nature. Artificial live rock is designed to mimic natural living rock which is capable of being a substrate for corals, a habitat for epibenthic and the biological filter of a saltwater aquarium. The purpose of this research is to know the technique of making artificial live rock and the development of artificial live rock that are suitable for export on an export scale. The method used in this research is an experimental method with quantitative descriptive analysis. The level of suitability and product standards uses a simultaneous regression coefficient test analysis or the F test. The manufacture of artificial live rock does not have a special pattern, but artificial live rock is made as attractive as possible and resembles the shape in nature. Product standardization is carried out by using artificial live rock materials consisting of: 1 kg of pumice stone, ½ kg of cement, ½ kg of sand, 500 grams of calcium and 1.5 liters of water. The type of substrate that is good and ideal for algae on the surface of artificial live rock is an area with a bottom of coral sand mixed with coral rubble. Artificial live rock can be harvested for 3 months in water, with the characteristics of the surface of the artificial live rock covered algae which is then cleaned and placed in a treatment pond before being exported